AgroEcoIndex periurbano. Una herramienta para evaluar la gestión ambiental en establecimientos hortícolas - D´Angelcola, María Elena; Frank, Federico Carlos; Delprino, Maria Rosa; Matoff, Evangelina; Constantino, Armando Roberto; Ricard, Florencia; Mitidieri, Mariel Silvina (2024)
Póster